Structure-based design of UDP-GlcNAc analogs as candidate GnT-V inhibitors - Vibhute, Amol M.; Tanaka, Hide-nori; Mishra, Sushil K.; Osuka, Reina F.; Nagae, Masamichi; Yonekawa, Chizuko; Korekane, Hiroaki; Doerksen, Robert J.; Ando, Hiromune; Kizuka, Yasuhiko (Biochimica et biophysica acta. General subjects, 2022)
Background: N-Glycan branching regulates various functions of glycoproteins. N-Acetylglucosaminyltransferase V (GnT-V) is a GlcNAc transferase that acts on N-glycans and the GnT-V-producing branch is highly related to cancer progression. This indicates that specific GnT-V inhibitors may be drug candidates for cancer treatment. To design novel GnT-V inhibitors, we focused on the unique and weak recognition of the donor substrate UDP-GlcNAc by GnT-V. On the basis of the catalytic pocket structure, we hypothesized that UDP-GlcNAc analogs with increasing hydrophobicity may be GnT-V inhibitors. Methods: We chemically synthesized 10 UDP-GlcNAc analogs in which one or two phosphate groups were replaced with hydrophobic groups. To test these compounds, we set up an HPLC-based enzyme assay system for all N-glycan-branching GlcNAc transferases in which GnT-I–V activity was measured using purified truncated enzymes. Using this system, we assessed the inhibitory effects of the synthesized compounds on GnT-V and their specificity. Results: Several UDP-GlcNAc analogs inhibited GnT-V activity, although the inhibition potency was modest. Compared with other GnTs, these compounds showed a preference for GnT-V, which suggested that GnT-V was relatively tolerant of hydrophobicity in the donor substrate. Docking models of the inhibitory compounds with GnT-V suggested the mechanisms of how these compounds interacted with GnT-V and inhibited its action. Conclusions: Chemical modification of the donor substrate may be a promising strategy to develop selective inhibitors of GnT-V. General significance: Our findings provide new insights into the design of GnT inhibitors and how GnTs recognize the donor substrate. •GnT-V is a cancer-related glycosyltransferase forming a GlcNAc branch in N-glycans.•Recognition of the donor substrate UDP-GlcNAc by GnT-V is unique and weak.•Ten UDP-GlcNAc analogs were chemically synthesized as potential GnT-V inhibitors.•Some of these compounds inhibited GnT-V activity.